Transforming Stress To Happiness: Implementation of the I-Message Technique for Establishing Positive Communication Patterns in the Family - Muhyatun Muhyatun (Da'wa Faculty of Islamic State University Salatiga, 2022)
Smooth communication is an absolute factor that is needed in building a family and living a household life. Communication can be a means when someone wants to change the attitudes, opinions, or behavior of himself and others. Communication aims to help all family members express their feelings, such as feelings of happiness, sadness, desire to be heard, and the like. With good communication, various changes will be made, especially concerning family life. The success of communication in the family is also directly proportional to the harmony of the environment in this microsystem. If the communication between family members is positive, then the environmental harmony created is also positive, and vice versa. This study was conducted to provide an overview of the use of i-message techniques in forming positive communication patterns in a family. The research method used is a literature review. The results of the research conducted showed that the i-message technique helped build positive communication in the family. The application of this communication technique is carried out in the immediate family and extended family. In the immediate family, it is focused on communication between husband and wife, and both as parents and children (parenting), which is done by reducing the habit of you-message conversation and applying the three principles in Thomas Gordon's Parent Effectiveness Training Books. Then in big family communication patterns, it can be done by reducing you-message conversations and the suitability of time and conditions.